2009
DOI: 10.1359/jbmr.090207
|View full text |Cite
|
Sign up to set email alerts
|

Hip Fracture Patients at Risk of Second Hip Fracture: A Nationwide Population-Based Cohort Study of 169,145 Cases During 1977–2001

Abstract: In patients with prior hip fracture (HFx), little is known about time frame and risk factors of second HFx, as well as the ensuing mortality. The aim of the study was to elucidate the incidence of second HFx and subsequent mortality. All 169,145 patients with a first HFx in Denmark during 1977-2001 were followed for up to 25 yr and compared with the background population. Data on fractures, vital status, comorbidity, redeemed prescriptions, and socio-demographic variables were retrieved from national registers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
185
3
15

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(215 citation statements)
references
References 72 publications
(162 reference statements)
12
185
3
15
Order By: Relevance
“…The same relative risks were found in men and women, though the absolute risk was higher in women. This transient phenomenon will be missed in long-term follow-up studies where the pattern of risk with time is not studied [2,[19][20][21]. Several previous studies have found that a recent occurrence of fracture was a greater risk factor for subsequent fracture than a history of earlier fracture, demonstrated for vertebral fracture [6,11], hip, humeral and forearm fractures [3,6] and all fractures combined [12].…”
Section: Discussionmentioning
confidence: 99%
“…The same relative risks were found in men and women, though the absolute risk was higher in women. This transient phenomenon will be missed in long-term follow-up studies where the pattern of risk with time is not studied [2,[19][20][21]. Several previous studies have found that a recent occurrence of fracture was a greater risk factor for subsequent fracture than a history of earlier fracture, demonstrated for vertebral fracture [6,11], hip, humeral and forearm fractures [3,6] and all fractures combined [12].…”
Section: Discussionmentioning
confidence: 99%
“…(24)(25)(26)(27)(28)(29)(30)(31) Therapeutic agents that reduce fracture risk rapidly are desirable for these patients.…”
Section: Goal-directed Selection Of Initial Therapymentioning
confidence: 99%
“…Так, доведеними факторами ризику переломів ПВСК вважають вік старше від 65 років, належність до жі-ночої статі, попередні переломи в анамнезі, схиль-ність до падінь, сімейний анамнез переломів ПВСК, тривалий прийом глюкокортикоїдів, зловживання алкоголем, дефіцит вітаміну D та наявність деяких соматичних захворювань, зокрема паркінсонізму, цукрового діабету ІІ типу, ревматоїдного артриту та ін. [3,[13][14][15][16][17][18][19][20].…”
Section: âñòóïunclassified
“…Розподіл показника 10-річної ймовірності переломів стегнової кістки в чоловіків та жінок до перелому ПВСК вікових груп більш часто зустрічаються переломи кісток передпліччя, зокрема переломи Колліса, а переломи тіл хребців більш характерні для осіб літного віку. Обидва види переломів у декілька разів збільшують частоту по-вторних переломів, а також інших остеопоротичних пе-реломів [16][17][18][19].…”
Section: îáãîâîðåííÿunclassified
See 1 more Smart Citation